Legal Protection for Notaries Managing Protocols of Other Notaries: A Preventive and Repressive Approach in Indonesia - Zen, Ariesta Putry Salsabila; Tjoanda, Merry; Uktolseja, Novyta (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Legal protection for notaries who hold other notary protocols is a crucial issue in the Indonesian legal system to maintain the integrity of authentic deeds. Purposes of the Research: This research aims to analyze the responsibilities and forms of preventive and repressive legal protection for notaries who receive the protocol. Methods of the Research: Using normative research methods with legislative and conceptual approaches, this study examines primary, secondary, and tertiary legal sources. Findings of the Research: The main findings show that preventive protection is inadequate in the Law on Notary Offices related to the submission of protocols, while repressive protection through civil and criminal law mechanisms faces challenges in proving errors. This study identifies that the Notary Position Law needs to be clarified regarding the limitations of the responsibility of notaries who receive the protocol, especially related to negligence that occurred before the protocol was submitted. The contribution of this research is to provide concrete recommendations for the improvement of regulations to create legal certainty and notary professionalism in the management of vital state archives